A theoretical framework for product relationships description over space and time in integrated design. Issue 4 (27th May 2016) - Gruhier, Elise; Demoly, Frédéric; Kim, Kyoung-Yun; Abboudi, Said; Gomes, Samuel
ABSTRACT: This paper presents a novel qualitative description theory in the context of integrated design, which here incorporates assembly sequence planning in the early product design stages (also called assembly oriented design – AOD). Based on a literature review of current AOD approaches, product models and mereotopology-based theories, the authors introduce a promising mereotopological theory which enables the formal product relationships description in integrated design by introducing an emerging framework, four-dimensionalism (i.e. perdurantism in philosophy). The proposed efforts aim at providing a concrete basis for describing the evolution of spatial entities (i.e. product parts) and their relationships over time and space during the design phases by considering their related assembly processes. In product design, the interpretation of engineering reality from a perdurantist point of view leads to a seamless consideration of relationships between spatial, temporal and spatiotemporal dimensions. Indeed, with such a mereotopological theory, formal product design description is enabled by proactively considering its assembly sequence from a temporal point of view in the early stages of the product development process, and ensures information and knowledge consistency over space and time. Finally, an ontological implementation is presented within Protégé through a mechanical assembly as a case study, so as to illustrate the applicability and the relevance of the theory.